The Correlation Between Teaching-Learning Quality and Students` Motivation to Study in Yogyakarta`S Bimbel - Ciptro Handrianto; Sabri Mohd Salleh; Jamilu Mustapha Chedi (Universitas Negeri Padang, 2020)
After taking The National Examination Test, some senior high school students apply to Bimbel (Learning Service Centre) in Yogyakarta and leave Bimbel in their provinces instead. The purpose of this study was to examine the correlation between the teaching-learning quality of Yogyakarta`s Bimbel and students` motivation from outside Java Island for choosing Yogyakarta`s Bimbel to prepare pre-college study. The study used a quantitative method by using SPSS to analyze statistical descriptive and correlation data. There were 107 respondents from various provinces in Indonesia involved in this study. A study found that the majority of respondents agreed that the teaching-learning quality in Yogyakarta`s Bimbel helped them to enter the top-10 universities in Indonesia. Students have a high motivation to study in Yogyakarta`s Bimbel. There is a strong correlation between the teaching-learning quality of Yogyakarta`s Bimbel and students` motivation to study. The conclusions of this study are: (1) The majority of students agree that the teaching-learning quality of Yogyakarta`s Bimbel is better than their own province; (2) Students` motivation to study in Yogyakarta`s Bimbel is high; And (3) There is a strong relationship between teaching-learning quality and students` motivation to study in Yogyakarta`s Bimbel.Keywords: Teaching-Learning Quality, Students` Motivation, Yogyakarta`s Bimbel